2017
DOI: 10.1002/asia.201700688
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Boron Phosphate as an Efficient Catalyst for Epoxide Activation to Synthesize Cyclic Carbonates with CO2

Abstract: Development of inexpensive, easily prepared, non-toxic, and efficient catalysts for the cycloaddition of CO with epoxides to synthesize five-membered cyclic carbonates is a very attractive topic in the field of CO transformation. In this work, we conducted the first work on the cycloaddition of CO with epoxides to produce cyclic carbonates catalyzed by a binary catalyst system consisting of KI and boron phosphate (BPO ), which are both inexpensive and non-toxic, and various corresponding cyclic carbonates coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Pioneering contributions in this area include the codimerization of isoprene with CO 2 firstly disclosed by Hoberg, and the copolymerization of epoxides with CO 2 initially reported by Inoue [10,11]. In addition, the latest progress examples include the synthesis of salicylic acid from the reaction of phenol salts with CO 2 [12][13][14], the hydrogenation of CO 2 with hydrogen to formic acid (HCO 2 H) [15][16][17][18][19][20][21][22][23][24][25][26][27], methanol [28], ethanol [29], the carboxylation of olefin with CO 2 to acrylic acids catalyzed by coinage-metal-based catalysts [30][31][32][33][34], the cycloaddition of CO 2 with epoxides to give cyclic carbonates [35][36][37][38][39][40][41][42][43], and the reaction of CO 2 with amines to afford carbamates [44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering contributions in this area include the codimerization of isoprene with CO 2 firstly disclosed by Hoberg, and the copolymerization of epoxides with CO 2 initially reported by Inoue [10,11]. In addition, the latest progress examples include the synthesis of salicylic acid from the reaction of phenol salts with CO 2 [12][13][14], the hydrogenation of CO 2 with hydrogen to formic acid (HCO 2 H) [15][16][17][18][19][20][21][22][23][24][25][26][27], methanol [28], ethanol [29], the carboxylation of olefin with CO 2 to acrylic acids catalyzed by coinage-metal-based catalysts [30][31][32][33][34], the cycloaddition of CO 2 with epoxides to give cyclic carbonates [35][36][37][38][39][40][41][42][43], and the reaction of CO 2 with amines to afford carbamates [44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it is a low‐cost catalyst. The first study on epoxides catalyzed by BPO 4 was reported by Xue et al [27] . They proposed that the BPO 4 catalyst plays a role in activating the epoxy ring by forming hydrogen bonds with Brønsted acidic sites and simultaneously interacting with Lewis acidic sites on the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…However, limitations of product separation and catalyst recycling are of real concern in the homogeneous catalytic reaction. These limitations have been tackled to a great extent by the utilization of heterogeneous catalysts that include metal oxides, coordination complexes, zeolites, and functional polymers, which display a low activity under ambient conditions or leaching …”
Section: Introductionmentioning
confidence: 99%
“…CO 2 has attracted the attention of researchers in recent times as a carbon source for several organic transformations because it is an abundant, renewable, and safe C1 feedstock that is easy to handle, nonflammable, and nontoxic . Transformations of CO 2 , such as CO 2 fixation reactions with epoxides to yield five‐membered cyclic carbonates, have been well‐established with various homo‐ and heterogeneous catalysts that include metal oxides, coordination complexes, and supported ionic liquids . The green catalytic conversion of a C1 feedstock readily available from combustion into value‐added cyclic carbonates that can be applied as a raw material for cosmetics, intermediates in the synthesis of ethylene glycol, acyclic carbonates, pharmaceuticals, polymers, and as an electrolyte in batteries has been reported .…”
Section: Introductionmentioning
confidence: 99%